Aspectos de la germinacion del Juniperus oxycedrus L. - Pardos, J.A.=700 1 Lazaro, G.
(En, Es)
Ilus., 16 ref.
Keywords: JUNIPERUS; GERMINACION; SEMILLA; ESPAÑA; JUNIPERUS OXYCEDRUS; ANALES DEL I.N.I.A.